Balancing health and economic livelihoods: Policy responses to the COVID-19 pandemic in Zambia - Malambo, Miyanda; Singogo, Fwasa; Kabisa, Mulako; Ngoma, Hambulo (International Food Policy Research Institute, 2020)
In response to the global coronavirus (COVID-19) pandemic, countries across the world have instituted various policy measures which-although different in their approaches-are all evolving as the pandemic progresses. This brief uses data collected under the COVID-19 Policy Response (CPR) project to report on the policy responses in Zambia during the initial six months of the pandemic (IFPRI 2020).